“HISTORY AND CULTURE OF ANCIENT AND MODERN POPULATIONS FROM INNER ASIA” - Program of the International Conference (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2010)
15-16 September, 2010, Ulaanbaatar, Mongolia